KEBEBASAN TOKOH PEREMPUAN DALAM NOVEL PADA SEBUAH KAPAL KARYA N.H. DINI: KAJIAN FEMINISME - Nensilianti, Nensilianti; Ridwan, Ridwan; Shalsabilah Z, Shafira (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2024)
Women are complex creatures with diverse lives, thus giving rise to a continuous and broad discourse on women's studies. Various approaches are taken to achieve women's liberation, and one of these approaches is the use of literary works. This article aims to examine women's freedom in the novel "Pada Sebuah Kapal" by N.H. Dini using feminist studies. The research method used is qualitative with feminist analysis techniques. The results of the study show that the novel "Pada Sebuah Kapal" focuses on the depiction of women and their rights. Solidarity among women and efforts to rebel against social expectations, this novel encourages deep reflection on the role of women and their rights in a patriarchal society. This is illustrated in quotes that show women's freedom over themselves, and households, women's freedom in education, and women's freedom in the economic field, as well as in communication.